Investigation of Psychosocial, Clinical Outcomes of Individuals with Limb Loss After Earthquakes. - Sehlikoğlu, Şeyma; Çiçek, Necati (Journal of Loss & Trauma)
The purpose of this study is to investigate the severity of symptoms of Post-Traumatic Stress Disorder (PTSD), depression, psychache, and coping styles in individuals who have experienced limb loss or have not sustained any permanent injuries while trapped under rubble following an earthquake. Furthermore, the study aims to explore the differences between groups in terms of sociodemographic and event characteristics. The study included individuals who were trapped under rubble during the earthquake and had a limb amputated, as well as those who were trapped under rubble but did not experience any permanent physical function loss. Semi-structured sociodemographic form, PTSD Checklist for DSM-5 (PCL-5), Psychache Scale, Coping with Earthquake Stress Scale (CESS), and Beck Depression Inventory (BDI) assessment tools were used. A total of 64 participants, 32 with and 32 without limb loss, were included in the study. It was found that the severities of traumatic stress and depressive symptoms and psychache were significantly higher in the earthquake survivors with limb loss than those without limb loss (p < 0.001, p < 0.001, and p = 0.005, respectively). It was found that earthquake survivors with limb loss made fewer positive reappraisals than those without limb loss (p = 0.012). According to the multiple linear regression analysis, having limb loss predicted BDI and PCL-5 scores (β = -12,239, p < 0,001; β = -10,105, p = 0,008, respectively). Additionally, suicidal ideation exacerbates the severity of psychache in individuals who are were trapped under rubble. Identifying the factors related to the mental state of these individuals is useful for determining those who are most likely to need psychological support.